Habitat selection by bull elephants in central Zimbabwe - Ferrel Osborn (Pachyderm)
This two year study in the Sebungwe region of Zimbabwe assessed the habtiat preferences and utilization of bull elephants. 16 bulls radio collared were monitored and their recorded locations plotted om a maps overlays the vegetation the region. The animals showed no significant seasonal preferences but 4 of the 8 vegetation types were more heavily utilized. There was a tendency for the elephants utilize Julbernardia-Vellozia woodlands and grasslands, Brachystegia-Combretum bush and Colospermum mopane woodlands more heavily, but they also spend quite a time of time in the miombo woodland sections. The author notes 'This technique may prove useful for examining habitat preference with regards to making management decisions'.